Exclusive breastfeeding status of children aged between 6 and 24 months in the nomadic population of Hadaleala district, Afar Region, northeast Ethiopia - Zemichael Gizaw; Wondwoson Woldu; Bikes Destaw Bitew (BMC, 2017)
Abstract Background Exclusive breastfeeding (EBF) during infancy is fundamental, however it is not fully practiced in the nomadic population of Ethiopia. In Ethiopia, there is still a lack of information on the implementation of the EBF, especially among the nomadic population. This study was conducted to assess the EBF status of children during their first 6 months of life, who are now aged between 6 and 24 months, in the nomadic population of Afar region. The study also aimed to identify factors affecting exclusive breastfeeding. Methods A community based cross-sectional study was conducted from April to May, 2015 to assess EBF of children aged between 6 and 24 months during the first 6 months of life. Exclusive breastfeeding is defined as consuming only breast milk (including expressed breast milk) during the first 6 months and no other liquids and solid foods except medications, and non exclusive breastfeeding is taking liquids and solid foods in addition to breast milk. The cluster sampling technique was used to select the study participants. Data were collected from 254 households using a structured questionnaire. Results One hundred eighty eight of the children were fed breast milk exclusively for the first 6 months of age; the rate of EBF in the study area was 74% (95% CI 70, 78%). One hundred fifty four (60.6%) of the children received breast milk within 1 h immediately after birth and 207 (81.5%) of the children maintained breastfeeding at the time of the survey. Exclusive breastfeeding was statistically associated with mothers aged above 35 years (AOR 8.3, 95% CI 1.7, 40.3), commencing to breastfeed in first hour (AOR 3.5, 95% CI 1.8, 6.9), and parents who didn't migrate or move to a more comfortable area (AOR 4.6, 95% CI 1.5, 14.4). Conclusion Exclusive breastfeeding was not fully practiced in the study area. Therefore, promotion of infant and young children feeding (IYCF) is needed in the area to strengthen EBF practices. Moreover, child feeding practices should be integrated with the existing health system and attention should be given to the nomadic mothers.